2005
DOI: 10.1081/jdi-56630
|View full text |Cite
|
Sign up to set email alerts
|

Diltiazem Attenuates Oxidative Stress in Diabetic Rats

Abstract: Diabetic nephropathy is the main cause of end stage renal damage. Oxidative stress is involved in the etiology of diabetic nephropathy and intracellular calcium is reported to play a considerable role in the development of renal damage in the diabetic kidney. Calcium antagonism can slow the progression of renal impairment in diabetes. The present study was thus designed to examine the effect of a nondihydropyridine calcium channel blocker, diltiazem, on renal function, oxidative stress, and nitric oxide (NO) r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 45 publications
2
3
1
Order By: Relevance
“…ABT-627 treatment of sham rats also decreased ED-1-positive cells in the renal cortex; however, it is not clear whether the mechanism is similar in sham and hyperglycemic rats. Although renal hypertrophy was evident in HG rats, we did not observe significant structural changes in the kidney during this study, although some previous reports have shown glomerular enlargement, matrix expansion, interstitial fibrosis, and arteriolopathy during early diabetes in the STZ model (33)(34)(35)(36). These differences may be due to the strain or gender of rats used or the use of insulin to maintain moderate hyperglycemia.…”
Section: Discussioncontrasting
confidence: 51%
“…ABT-627 treatment of sham rats also decreased ED-1-positive cells in the renal cortex; however, it is not clear whether the mechanism is similar in sham and hyperglycemic rats. Although renal hypertrophy was evident in HG rats, we did not observe significant structural changes in the kidney during this study, although some previous reports have shown glomerular enlargement, matrix expansion, interstitial fibrosis, and arteriolopathy during early diabetes in the STZ model (33)(34)(35)(36). These differences may be due to the strain or gender of rats used or the use of insulin to maintain moderate hyperglycemia.…”
Section: Discussioncontrasting
confidence: 51%
“…ICV-STZ-induced rats exhibited an increase in LPO as measured by TBARS levels and decreased the GSH and SOD levels significantly. DTZ at 10, 20, and 40 mg/kg dose-dependently restored the altered enzyme status, which agreed with earlier studies that DTZ significantly attenuated oxidative stress in STZ-induced diabetic rabbits and aluminum chloride-induced oxidative stress in mice [29,64].…”
Section: Discussionsupporting
confidence: 92%
“…17,18,22 High serum glucose levels promote the oxidative stress within the tissues via increasing the reactive oxygen radicals (ROS) through mitochondrial electron transfer chain. 19 ROS are highly toxic to cells, the pathogenesis of this system has been shown to increase lipid peroxidation and nuclear factor kappa b along with transforming growth factor b that causes tissue fibrosis Notes: *p50.05.…”
Section: Discussionmentioning
confidence: 99%